The Impact Of Digital Tax On Msme Growth In Indonesia: Evidence From 2021–2025 - Irena Mei Darnis Halawa; Silvia Putri Febriend; Achmad Fauzi Rifai; Ngatimin Ngatimin (Asosiasi Dosen Muda Indonesia, 2025)
This study explores the influence of digital taxation on the growth of micro, small, and medium enterprises in Indonesia within the context of the recent transition toward a more digitized economy. Using a mixed methods approach, the research combines survey data with in-depth interviews to capture both quantitative and qualitative insights. The findings indicate that digital tax understanding, implementation practices, and perceived business impacts are closely associated with enterprise development, particularly in enhancing operational efficiency, formalization, and access to financial services. Qualitative evidence highlights that while digital tax compliance promotes greater accountability and competitiveness, challenges remain regarding limited literacy, adaptation costs, and regulatory complexity. The study emphasizes the need for simplified procedures, supportive policies, and structured education programs to ensure that digital taxation contributes positively to sustainable economic growth. These results provide implications for policymakers, tax authorities, and practitioners engaged in fostering a more inclusive fiscal environment.